2020
DOI: 10.1002/hep4.1483
|View full text |Cite
|
Sign up to set email alerts
|

Primary Alcohol‐Activated Human and Mouse Hepatic Stellate Cells Share Similarities in Gene‐Expression Profiles

Abstract: Alcoholic liver disease (ALD) is a leading cause of cirrhosis in the United States, which is characterized by extensive deposition of extracellular matrix proteins and formation of a fibrous scar. Hepatic stellate cells (HSCs) are the major source of collagen type 1 producing myofibroblasts in ALD fibrosis. However, the mechanism of alcohol‐induced activation of human and mouse HSCs is not fully understood. We compared the gene‐expression profiles of primary cultured human HSCs (hHSCs) isolated from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…RNA sequencing was performed at La Jolla Institute for Immunology and described previously. 40 Sequenced reads were aligned to the mouse genome (National Center for Biotechnology Information, MGSCv38, mm10) using STAR (Spliced Transcripts Alignment to a Reference). 41 Read quantification was performed with RSEM3 v1.3.0 (University of Wisconsin, Madison, WI) and Ensembl annotation (Gencode v19, Wellcome Genome Campus, Hinxton, Cambridgeshire, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA sequencing was performed at La Jolla Institute for Immunology and described previously. 40 Sequenced reads were aligned to the mouse genome (National Center for Biotechnology Information, MGSCv38, mm10) using STAR (Spliced Transcripts Alignment to a Reference). 41 Read quantification was performed with RSEM3 v1.3.0 (University of Wisconsin, Madison, WI) and Ensembl annotation (Gencode v19, Wellcome Genome Campus, Hinxton, Cambridgeshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing was performed at La Jolla Institute for Immunology and described previously. 40 Sequenced reads were aligned to the mouse genome (National Center for Biotechnology Information, MGSCv38, mm10) using STAR Q41…”
Section: Rna Sequencingmentioning
confidence: 99%
“…However, the mechanism of alcohol-induced activation of human and mouse HSCs is not fully understood 6) . To validate mouse model of toxic fibrosis, primary alcohol-activated human HSCs (hHSCs, isolated from patients with ALD or without underlying liver disease) and mouse HSCs (mHSCs, from mice subjected to carbon tetrachloride (CCl4), isolated from intragastric alcohol-fed or pair-fed mice), and their gene expression profiles were compared using RNA-Seq 7,8) . Comparative transcriptome analysis revealed that both, alcohol-activated hHSCs and mHSCs, and CCl4-injured mHSCs share expression of Col1a1, Acta1, PAI-1, TIMP1 and LOXL2 9) .…”
Section: St Sessionmentioning
confidence: 99%
“…While abstinence from alcohol has proven beneficial at reversing fibrosis [ 106 ], the underlying genomic changes in alcoholic cirrhosis are poorly understood. In one study, mice and human cultured HSCs were compared using single-cell RNA-seq; CSF1R, PLEK, LAPTM5, CD74, CD53, MMP9, CD14, CTSS, TYROBP, and ITGB2 were upregulated in both alcohol-induced mouse HSCs and alcohol liver disease HSCs [ 107 ]. GWAS studies of a Mestizo Mexican and European Caucasian cohorts found the SNP rs738409 in PNPLA3 to be linked with alcoholic liver disease, similar to NAFLD [ 108 , 109 ].…”
Section: Hepatic Fibrosismentioning
confidence: 99%